A new service for central laboratory, UMP: developing eurycomanone as a chemical marker for testing and standardizing Tongkat Ali products - Vejayan, Jaya; Yusoff, M. M.; Maniam, Gaanty Pragas (2016)
Eurycoma longifolia is widely known for their aphrodisiac properties. Due to this, abundant of the E. longifolia based products are sold in the market without any specific regulation to control the quality and authentication of E. longifolia product. The only marker can be used to detect the presence of E. longifolia is eurycomanone. This study is to develop a method for the Central Laboratory of Universiti Malaysia Pahang to determine the presence and quantity of eurycomanone content in herbal products manufactured with Tongkat Ali. The analysis was carried out using RP-HPLC at 245nm with isocratic mobile phase that comprised of acetonitrile and water (86:14) with a flow rate is 0.8ml/min. The separation was done using Zorbex SB-C18 column (5μm, 250mm X 4.6mm) and injection volume is 10μl. Validation tests of the method is performed to indicate the linearity, accuracy, precision, limit of detection (LOD) and limit of quantification (LOQ). The result indicated that the linearity was in the range of 0.01325-0.5 mg/ml (R2=0.9997). The precision of retention time and peak area for intraday analysis of eurycomanone standard in relative standard deviation is <0.15 and <0.50 %; the precision of retention time and peak area for interday is <0.55 and <6.60%, respectively. The accuracy as the percent recovery of eurycomanone was in the range of 94.60-104.67%, while LOD and LOQ were 0.0196 and 0.0593, respectively. The concentration of eurycomanone in E. longifolia freeze dried crude water extract is 0.82±0.05w/w% and herbal products is around 0.06±0.00-0.30±0.00w/w%. The proposed method shows a good linearity, accurate, precise, reproducibility and short elution time. This method can be an affordable approach for the quality control of E. longifolia crude extract and its herbal products for any small and medium sized entrepreneurs of Tongkat Ali having no QC laboratory of their own.